2019
DOI: 10.1088/1367-2630/ab5a9b
|View full text |Cite
|
Sign up to set email alerts
|

Controllable high-speed polariton waves in a PT-symmetric lattice

Abstract: Parity-time (PT) symmetry gives rise to unusual phenomena in many physical systems, presently attracting a lot of attention. One essential and non-trivial task is the fabrication and design of the PTsymmetric lattices in different systems. Here we introduce a method to realize such a lattice in an exciton-polariton condensate in a planar semiconductor microcavity. We theoretically demonstrate that in the regime, where lattice profile is nearly PT-symmetric, a polariton wave can propagate at very high velocity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Particularly, a chaotic excitonpolariton billiard has been demonstrated to exhibit multiple non-Hermitian spectra where the EP physics can be explored (see figure 17(a)) [253,254]. Similar non-Hermitian concepts have been extended to different platforms and degrees of freedom in exciton-polariton systems, such as two dipole modes in a non-Hermitian resonator (see figure 17(d)) [255,256] and synthetic band-structure engineering [257,258]. Specifically, two coupled semiconducting micropillars can form a bosonic Josephson junction that supports PT phase transitions and EPs [259].…”
Section: Plasmonics and Exciton-polaritons-based Systemsmentioning
confidence: 99%
“…Particularly, a chaotic excitonpolariton billiard has been demonstrated to exhibit multiple non-Hermitian spectra where the EP physics can be explored (see figure 17(a)) [253,254]. Similar non-Hermitian concepts have been extended to different platforms and degrees of freedom in exciton-polariton systems, such as two dipole modes in a non-Hermitian resonator (see figure 17(d)) [255,256] and synthetic band-structure engineering [257,258]. Specifically, two coupled semiconducting micropillars can form a bosonic Josephson junction that supports PT phase transitions and EPs [259].…”
Section: Plasmonics and Exciton-polaritons-based Systemsmentioning
confidence: 99%
“…In an excitation regime where polaritons behave like bosonic quasi-particles, they can experience condensation and show spontaneous macroscopic coherence under nonresonant excitation, as shown in Figure (a). Thanks to the spontaneous decay of photons from the microcavity, polaritons are inherently driven-dissipative in nature and as such offer the ability to study PT symmetry , and non-Hermitian physics. , Also in a coupled polariton microresonator it was demonstrated that relaxation kinetics plays a crucial role in the condensation process under asymmetric pumping . Polariton dimers can be used to explore polariton–polariton nonlinear interactions with Josephson oscillations, quantum self-trapping, interplay of interference and nonlinearity, and bistability .…”
Section: Introductionmentioning
confidence: 99%
“…1(a). Thanks to the spontaneous decay of photons from the microcavity, polariton systems are inherently driven-dissipative in na- ture and as such provide an excellent platform to study PT symmetry [23] and non-Hermitian physics. In our previous works [24,25] we demonstrated that the polariton condensate wavefunction and energy distribution can be strongly modified by the gain and loss coefficients in an optical billiard.…”
mentioning
confidence: 99%